Surgical management of agenesis of the vulva with atresia ani-et-distal recti in a heifer calf: A case report - Wamaitha, Moses N; Kihurani, David O; Kimeli, Peter; Mwangi, Willy E; Mande, John D (Journal of Advanced Veterinary and Animal Research, 2015)
Successful surgical intervention of atresia ani-etdistal recti with agenesis of vulva in a heifer calf is reported in this paper. The calf aging 1-day was presented with a history of swelling at the perineal region. In clinical examination, both vulval and anal openings were found absent. Initial surgical operation under sedation and local anesthesia was done to correct these abnormalities. As a result, the calf could urinate, but attempted defecation was not successful. Surgical operation was done again at the anal region to resolve this condition. Post-operatively, tetracycline spray was applied on both surgical wounds immediately after surgery, and repeated twice daily for 10 days. Amoxicillin trihydrate (at 750 mg/kg bwt) and Phenylbutazone (at 400 mg/kg bwt) were administered intramuscularly once, and the treatment was repeated on every alternate day up to 10 days of post-surgery. Finally, the calf was able to urinate and defecate normally, and the surgical wounds healed uneventfully within 14 days. http://dx.doi.org/10.5455/javar.2015.b95